1994
DOI: 10.1172/jci117228
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of microvascular blood flow in pancreatic islet isografts.

Abstract: There is evidence that intraislet cellular communication and hormone delivery within the islets of Langerhans is controlled via capillary perfusion directed from the B cell core to the A/D cell mantle (intraislet portal system). To determine whether vascularization of freely transplanted islets repeats this "coreto-mantle" capillary perfusion, hamster islets were isolated by collagenase digestion and transplanted into a skinfold chamber of syngeneic animals (n = 12). 14 d after transplantation, the microvascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 22 publications
2
77
0
Order By: Relevance
“…15,17,35 A biosynthetic collagen/polyester material showed a higher FVD as compared with polytetrafluorethylene synthetic material. It should be noted that the scaffold dimensions in that study (1 ϫ 1 ϫ 1 mm) differed from the dimensions used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…15,17,35 A biosynthetic collagen/polyester material showed a higher FVD as compared with polytetrafluorethylene synthetic material. It should be noted that the scaffold dimensions in that study (1 ϫ 1 ϫ 1 mm) differed from the dimensions used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that we limited the administration of sirolimus to the first 14 days posttransplantation, based on previous findings that islet engraftment initiates as early as on day 2 posttransplantation and concludes with the reestablishment of blood flow to islets grafts within 2-3 weeks in rodent models of diabetes (9,32). Strikingly, we found that sirolimus-mediated impairment in islet graft function was irreversible, as hyperglycemia, glucose intolerance, and hyperlipidemia persisted after discontinuation of sirolimus treatment at day 15 posttransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, unlike whole pancreas transplantation, islet grafts require the process of revascularization to establish adequate microvascular blood supply. 14,15 Isolated islets are reported to revascularize within 10-14 days after transplantation. 16 Vascular endothelial growth factor (VEGF) is a homodimeric protein comprised of four isoforms of 206, 189, 165 and 121 amino acids resulting from differential splicing.…”
Section: Introductionmentioning
confidence: 99%